2010
DOI: 10.1021/bm9013233
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of β-Cyclodextrin-Dextran Polymers by “Click” Chemistry

Abstract: Three series of novel water-soluble beta-cyclodextrin-dextran polymers have been prepared by "click" chemistry. The polymers were synthesized from alkyne-modified dextrans (AMDs) onto which mono-6-O-deoxy-monoazido-betaCD (N3betaCD) was grafted by a copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC). The polymers have been characterized by NMR spectroscopy and size exclusion chromatography (SEC). The binding properties have been characterized by isothermal titration calorimetry (ITC) and show excellent acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 35 publications
7
89
1
Order By: Relevance
“…[25] We showed that the excellent binding properties of these polymers are due to a high accessibility of the bCD cavities. Association constants as high as with bCD were determined at 25 8C in 0.05 mol Á L À1 NaCl solution (K % 1.2 Â 10 5 -2.05 Â 10 5 mol Á L À1 ).…”
Section: Binding Properties Of the Dextransmentioning
confidence: 89%
See 3 more Smart Citations
“…[25] We showed that the excellent binding properties of these polymers are due to a high accessibility of the bCD cavities. Association constants as high as with bCD were determined at 25 8C in 0.05 mol Á L À1 NaCl solution (K % 1.2 Â 10 5 -2.05 Â 10 5 mol Á L À1 ).…”
Section: Binding Properties Of the Dextransmentioning
confidence: 89%
“…The substitution degree was obtained by 1 H NMR in deuterated dimethyl sulfoxide (DMSO) from the ratio of the integration of the Ada protons (d ¼ 1.6-2.0) and of the integration of the anomeric and hydroxylic protons (d ¼ 4.4-5.0). The synthesis of the bCD grafted dextrans was recently reported [25] with their characterization [ 1 H NMR in deuterated water (Bruker DRX600) and size-exclusion chromatography]. The degree of substitution, the bCD content, and the number of bCD per chain are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cavasol R W7, with a molar substitution (per anhydro glucose unit) of 1.6-1.9 was a gift from Wacker Chemie AG (Burghausen, Germany). The water-soluble and biocompatible polymeric CDs have CDs as a part of the backbone [18][19][20] and were synthesized at the Section of Chemistry, Department of Biotechnology, Chemistry and Environmental Engineering, Aalborg University (Aalborg, Denmark) and used as received. The representative structure of the (-CD-PEG polymer is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%